2011
DOI: 10.1002/hec.1579
|View full text |Cite
|
Sign up to set email alerts
|

Does consumption of processed foods explain disparities in the body weight of individuals? The case of Guatemala

Abstract: Overweight/obesity, caused by the 'nutrition transition', is identified as one of the leading risk factors for non-communicable mortality. The nutrition transition in developing countries is associated with a major shift from the consumption of staple crops and whole grains to highly and partially processed foods. This study examines the contribution of processed foods consumption to the prevalence of overweight/obesity in Guatemala using generalized methods of moments (GMM) regression. The results show that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
99
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(106 citation statements)
references
References 35 publications
(36 reference statements)
4
99
0
3
Order By: Relevance
“…Buying in a supermarket is associated with a 23 percentage point lower probability (P < 0·001) of severe stunting. Control variables for these child/adolescent models were chosen based on the broad nutrition and health literature (16,19,(42)(43)(44)(45)(46) . Factors that contribute to overnutrition may be somewhat different from factors that contribute to undernutrition, which is why model specifications in Table 3 are not uniform for the different nutritional outcome variables.…”
Section: Impact Of Supermarket Purchase On Nutritional Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Buying in a supermarket is associated with a 23 percentage point lower probability (P < 0·001) of severe stunting. Control variables for these child/adolescent models were chosen based on the broad nutrition and health literature (16,19,(42)(43)(44)(45)(46) . Factors that contribute to overnutrition may be somewhat different from factors that contribute to undernutrition, which is why model specifications in Table 3 are not uniform for the different nutritional outcome variables.…”
Section: Impact Of Supermarket Purchase On Nutritional Statusmentioning
confidence: 99%
“…Several studies suggest that the spread of supermarkets leads to dietary changes for urban consumers (12,(15)(16)(17) . Most of this work shows that supermarket purchase is associated with increased consumption of energy-dense, processed foods (12,15,16) , although in one case supermarkets were found to increase dietary quality (17) . Research on the impact of supermarkets on consumer nutritional status in developing countries is rare.…”
mentioning
confidence: 99%
“…Findings from the studies in this special issue challenge that assertion and demonstrate an association between higher consumption of ultra-processed foods and poorer nutritional intakes, including higher intakes of energy and free/added sugar (9,11) and lower intakes of fibre (9) , micronutrients (9) and protein (8) . Epidemiological evidence has previously demonstrated that ultra-processed food consumption is associated with poorer diet quality in the USA (13) , Canada (14) and Brazil (15) ; obesity in Brazil (16) , Guatemala (17) , Spain (18) and Sweden (19) ; hypertension in Spain (20) ; metabolic syndrome in Brazil (21) ; and dyslipidaemia in children in Brazil (22) . Papers in this special issue reinforce the aetiology between ultra-processed food consumption and nutritional outcomes and chronic conditions, and extend such evidence to new populations.…”
mentioning
confidence: 99%
“…In any case, the rise of supermarkets and other modern retail outlets is associated with changing lifestyles and higher consumption of processed foods (Popkin, 2006;Hawkes, 2008;Asfaw, 2008;Asfaw, 2011;Rischke et al, 2014). Hence, the share of modern retail in grocery sales seem to be a suitable proxy for the nutrition transition.…”
mentioning
confidence: 99%